URGENSI FITUR HALAL FOOD PADA APLIKASI PENYEDIA MAKANAN DELIVERY ORDER - Ruslang (Universitas Mathla’ul Anwar Banten, 2025)
This study aims to explore the urgency of a halal food labeling feature in food delivery apps, particularly in addressing the needs of Muslim consumers in Indonesia. This study adopted a qualitative research method with a field approach, using direct observation and in-depth interviews involving 12 informants. The informants included app users, culinary entrepreneurs, and app developers. With the rapid development of digital technology, various business sectors are required to continuously innovate through the use of modern apps, including online food ordering services. Platforms such as GoFood, GrabFood, ShopeeFood, and other similar apps have now become part of the urban lifestyle. However, amidst the dominant Muslim population in Indonesia, the lack of a feature specifically indicating the halal status of food presents a challenge. This lack of clarity can raise concerns among Muslim consumers and limit their choices in accessing food that aligns with religious principles. Halal labels play a crucial role in assuring trust in a product. Therefore, the presence of halal information features in food delivery apps is an urgent need that cannot be ignored, to ensure the fulfillment of Muslim consumers' rights to food that aligns with their religious values.